(untitled) (CIPEEX, 2022)
THE ANKLE IS ONE OF THE JOINTS OF THE HUMAN BODY THAT SUFFER MOST FROM INJURIES, PLAYING AFUNDAMENTAL ROLE FOR THE FUNCTIONALITY OF THE INDIVIDUAL, WHICH IS THE SUPPORT OF BODY WEIGHT. ANKLE SPRAIN IS THE MOST COMMON DYSFUNCTION FOUND IN THIS FOLLOW-UP, ESPECIALLY IN FOOTBALL ATHLETES,LEADING TO A GLOBAL FUNCTIONAL DISABILITY, BEING DIVIDED INTO THREE DEGREES: MILD (I), MODERATE (II) AND SEVERE (III). THE STUDY IN QUESTION AIMS TO ASCERTAIN SCIENTIFIC EVIDENCE ON POSSIBLE TREATMENT METHODS, AIMING AT AN EARLY RETURN OF AFFECTED ATHLETES. THIS IS A NARRATIVE LITERATURE REVIEW, WITH A QUALITATIVE ASPECT, USING THE BVS, SCIELO AND PUBMED DATABASES. IT ISNOTEWORTHY THAT 5,177 STUDIES WERE FOUND RELATED TO THE DESCRIPTORS USED, WITH 72 STUDIES ELIGIBLE FOR READING. FROM THE READING OF THE ABSTRACTS 48 STUDIES WERE EXCLUDED, BEING INCLUDED 24 STUDIES THAT FIT THE INCLUSION CRITERIA. PHYSIOTHERAPEUTIC TREATMENT IN ANKLE SPRAINS IS NECESSARY, HAVING A SIGNIFICANT IMPORTANCE IN THE REHABILITATION OF ATHLETES AFFECTED WITH THIS DYSFUNCTION, SINCE IT IS A COMMON INJURY IN FOOTBALL PLAYERS. THERE ARE SEVERAL TREATMENT METHODS AVAILABLE FOR ANKLE SPRAINS THAT WILL ACT GLOBALLY ON THE PATIENT, AIMING AT AN IMPROVEMENT IN THEIR JOINT INSTABILITY, WEIGHT DISCHARGE, GAIT, BALANCE AND STRENGTH, PROVIDING THE ATHLETE WITH AN EARLY RETURN TO THEIR ACTIVITY. THE STUDY DEMONSTRATED SEVERAL TREATMENT METHODS FOR ANKLE SPRAIN AND THE IMPORTANCE OF PHYSIOTHERAPY IN THE REHABILITATION OF THOSE AFFECTED BY THIS DYSFUNCTION, BUT THERE IS NO SPECIFIC PHYSIOTHERAPEUTIC TREATMENT PROTOCOL IN GRADE I ANKLE SPRAIN IN FOOTBALL ATHLETES.